A role for CS-US contingency in Pavlovian conditioning. - Murphy, R; Baker, A (2004)
Two experiments evaluated the role of conditioned stimulus-unconditioned stimulus (CS-US) contingency in appetitive Pavlovian conditioning in rats. In both experiments, some groups received a positively contingent CS signaling an increased likelihood of the US relative to the absence of the CS. These groups were compared with control treatments in which the likelihood of the US was the same in the presence and absence of the CS. A trial marker served as a trial context. Experiment 1 found contingency sensitivity. There was a reciprocal relationship between responding to the CS and the trial marker. Experiment 2 showed that this result was not stimulus or response specific. These results are consistent with associative explanations and the idea that rats are sensitive to CS-US contingency.